Combined dealkylation and transalkylation reaction in FCC condition for efficient conversion of light fraction light cycle oil into value-added products. (15th November 2021) - Miao, Peipei; Zhu, Xiaolin; Zhou, Zhou; Feng, Xipan; Miao, Jie; Hou, Chenxiao; Li, Chunyi
Graphical abstract: Highlights: The dealkylation reactivity of MAHs in light fraction LCO with short chains is low. Benzene additive can contribute to the conversion of light fraction LCO. Appropriate mesopore and strong acid sites are needed for transalkylation reaction. The extra-framework aluminum of BEA zeolite can be removed by citric acid treatment. Abstract: The light fraction light cycle oil (LLCO) rich in alkyl-benzene and alkyl-naphthalene with short chains is expected to have a dealkylation reaction to produce value-added products. However, since the high bond energy of its side chains, low reactivity is inevitable under catalytic cracking circumstance. In this work, the catalytic cracking performance of 1, 2, 4, 5-TeMBs, as a model molecule of LLCO, was evaluated in FCC condition. Interestingly, the benzene additive can contribute to the conversion of 1, 2, 4, 5-TeMBs by transalkylation reaction. Based on this, we investigated the effect of benzene on the catalytic cracking of LLCO. Compared with the catalytic cracking of LLCO alone, higher reactivity of macromolecular alkyl-benzene and alkyl-naphthalene was achieved when benzene was used as an additive in LLCO. Meanwhile, a high yield of toluene was observed produced from the transalkylation reaction of benzene. Furthermore, several zeolite catalysts were evaluated for efficient conversion of a mixture of benzene and LLCO. The results indicated that the mesoporous BEA zeolite with the appropriate acidity property and mass transfer ability was regarded as the optimal catalyst given its highest yield of value-added products.